Pengaruh Enzim Amilase Brevibacterium sp dan Glukoamilase Terhadap Kemampuan Penjerapanan Minyak Pada Pati Singkong - Uzwatania, Fina; Rahma, Putri Ajeng Syahru; Pramasari, Dwi Ajias; Ningrum, Riska Surya; Sondari, Dewi (Universitas Sebelas Maret (UNS), 2023)
Improper oil waste management contributes to environmental degradation, notably water pollution. Because conventional methods for treating oil pollutants are costly and have limited removal efficacy, the use of natural adsorbents is recommended due to their dependability and affordability. The purpose of this study was to see how modified cassava starch affected oil adsorption using two types of enzymes: Brevibacterium sp amylase enzymes derived from Indonesian marine bacteria and commercial amylase enzyme (Dextrozyme® GA).Oil-adsorption degree is applied to several types of oil, including palm oil and olive oil. The findings revealed that the properties of modified starch differed from those of native starch in both physical and chemical terms. The modified starch produced by hydrolysis of the glucoamylase enzyme (Dextrozyme ® GA)had a yield of 80.16 %, reducing sugar content of 0.20 g/L at 24 h, and a particle size of 377 nm, which is lower than the starch hydrolyzed by Brevibacterium sp. In contrast, the degree of oil adsorption in the glucoamylase enzyme (Dextrozyme ® GA) is higher than Brevibacterium sp. Statistical analysis showed that the oil adsorption degree is affected by the type of enzyme, therefore, the modified starch from Brevibacterium sp still needs improvement to be competitive for oil adsorption compared with the modified starch from the glucoamylase enzyme (Dextrozyme ® GA).